Geographic Targeting in Urban Areas: A Social-Welfare Program for Older People in Mexico - Aguila, Emma (RAND Corporation, 2014)
This report details a comparison of the results of a social-gap index based on local and social observations at the block level with other marginalization and social-gap rates used to target social-welfare programs in Mexico. It also assesses the feasibility of targeting delivery of noncontributory pensions for older people who live in urban areas.